Pengaruh Kepribadian Dark Triad terhadap Perilaku Cyberbullying pada Pengguna Media Sosial - Annisa Tri Banowati; Suci Nugraha (UNISBA Press, 2022)
Abstract. Cyberbullying is the activity of people who persistently attack on the internet toward certain parties with various actions such as flaming, harassment, cyberstalking, denigration, impersonation, outing/trickery and exclution. Internet users in Indonesia are already in severe category in cyberbullying by being ranked as the fourth country with the most disrespectful internet users in Southeast Asia. This study intends to look at one of the factors that play a role in cyberbullying, namely personality. The personality that will be discussed in this research is the Dark Triad Personality. This research included 200 respondents of social media users on Instagram, Twitter and TikTok. The data was taken using Quota Sampling. The Dark Triad personality was measured using the Short Dark Triad 3 (Jones and Paulhus, 2014). Cyberbullying was measured using the Cyberbullying Scale (Safaria, 2020). In this study, there is a significant influence of the Dark Triad's personality on cyberbullying on social media users. (R-squared = 0.582) Abstrak. Cyberbullying adalah tindakan menyerang orang lain di internet secara terus-menerus secara sengaja dengan maksud menyudutkan pihak tertentu dengan terdapat beberapa aktivitas didalamnya seperti flaming, harassment, denigration, cyberstalking, impersonation, outing/trickery dan exclution.. Pengguna internet di Indonesia sudah termasuk kategori yang cukup parah dalam perilaku cyberbullying dengan menduduki peringkat ke-empat sebagai negara dengan pengguna internet paling tidak sopan se-Asia Tenggara. Penelitian ini bermaksud melihat salah satu faktor yang berperan pada perilaku cyberbullying yaitu kepribadian. Kepribadian yang akan dibahas pada penelitian ini adalah Kepribadian Dark Triad. Responden penelitian ini berjumlah 200 pengguna media sosial Instagram, Twitter dan TikTok. Data diambil menggunakan Quota Sampling. Kepribadian Dark Triad diukur menggunakan Short Dark Triad 3 (Jones and Paulhus, 2014). Perilaku cyberbullying diukur menggunakan Cyberbullying Scale (Safaria, 2020). Pada penelitian ini terdapat pengaruh yang signifikan antara kepribadian Dark Triad terhadap perilaku cyberbullying pada pengguna media sosial. (R-square= 0.582).